Praxeologische Feldforschung: Reichweite, Tragweite, Importanz und Relevanz als Analysekategorien - Geiselhart, Klaus; Runkel, Simon; Schäfer, Susann; Schmid, Benedikt (Geographica Helvetica, 2021)
This paper develops three analytical categories - range, supporting capacity, exigency/notability - to capture how supra-individual phenomena affect the people studied by empirical research. Researchers face a tension between constructivist and realist perspectives as the examined phenomena are simultaneously social constructs, in the way people perceive and understand them, and social facts in their consequences. Taking a critical perspective on the notion of large social phenomena - popularized by Theodore Schatzki - the paper develops an explorative terminology that aims to facilitate practice-oriented field research. Examples of empirical research on transition and degrowth initiatives illustrate how research subjects estimate the range of a phenomenon by trying to grasp whether they are in or out of its reach; the supportive capacity of a phenomenon by exploring how far it carries certain processes; and they experience the exigency of a phenomenon and ascribe a certain notability to it. Taken together, this terminology grasps the way phenomena are matters of concern, rather than matters of fact, for the research subjects.